2009
DOI: 10.1007/s10681-009-9999-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of resistance to lodging of landrace and improved cultivars in foxtail millet

Abstract: Lodging results in serious yield and quality reductions in foxtail millet (Setaria italica). Among summer crops, foxtail millet is a high density and soft stalked crop that is prone to lodging. Field selection for lodging resistance is difficult because the occurrence of lodging depends on the environmental conditions. A practical method for the evaluation of lodging is not available for foxtail millet, so an understanding of lodging-associated traits and identifying a suitable method to assess lodging are ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
0
18
1
Order By: Relevance
“…Lodging is a constraint in many crops, including finger and foxtail millets mainly due to soft stalk that are prone to lodging and crop management and environmental factors. In foxtail millet, Tian et al (2010) suggested lodging coefficient as a suitable indicator for field selection for lodging resistance. Foxtail millet landraces and improved varieties that resist lodging have been reported from China (Table 7.3).…”
Section: Lodgingmentioning
confidence: 99%
“…Lodging is a constraint in many crops, including finger and foxtail millets mainly due to soft stalk that are prone to lodging and crop management and environmental factors. In foxtail millet, Tian et al (2010) suggested lodging coefficient as a suitable indicator for field selection for lodging resistance. Foxtail millet landraces and improved varieties that resist lodging have been reported from China (Table 7.3).…”
Section: Lodgingmentioning
confidence: 99%
“…Numerous studies have reported variation in lodging resistance among genotypes of cereal crops, such as wheat (Easson et al 1993;Crook & Ennos 1994;Berry et al 2003a, b;Kelbert et al 2004a, b), barley (Hordeum vulgare L.) (Wang & Du 2001) and rice (Oryza sativa L.) (Ookawa & Ishihara 1992;Kashiwagi et al 2010), as well as foxtail millet (Tian et al 2010). In addition to genetic factors, damage from insects and/or diseases, together with rain and wind, can also increase the severity of stem-based lodging.…”
Section: Introductionmentioning
confidence: 99%
“…A cultivar with a low LC is expected to have reduced risk of lodging. The use of a LC to determine variation in stem-based lodging in cultivars and landraces of foxtail millet has been demonstrated: Tian et al (2010) found that stem-based lodging of foxtail millet was associated with stem-breaking strength (SBS), SFM (mechanical strength of stem) and the BM of above-ground parts and the roots. Plant height and internode length were closely related to stembased lodging in the landraces, but not in the modern improved cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Foxtail millet is also a major crop in the arid and semiarid region of India and is cultivated for bird feeding and forage production in Europe and North America. Among grass crops, foxtail millet belongs to the high‐density cultivated and soft‐stalked crops that are prone to lodging, which results in serious yield and quality reductions (Tian et al, 2010; Qian et al, 2012).…”
mentioning
confidence: 99%